2017
DOI: 10.1038/s41598-017-15987-1
|View full text |Cite
|
Sign up to set email alerts
|

Baseline and Breakthrough Resistance Mutations in HCV Patients Failing DAAs

Abstract: Sustained virologic response rates have increased dramatically following direct acting antiviral (DAA) therapy in chronic HCV infection. However, resistance-associated substitutions (RASs) may occur either prior to DAA or following drug exposure. The aim of this study was to determine RASs in DAA treatment-failing patients and the role of RASs in failure treatment. Six hundred and twenty HCV patients were evaluated. Direct sequencing of HCV genes was performed at breakthrough in all 31 patients failing DAAs, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 34 publications
6
24
0
Order By: Relevance
“…outcomes [11][12][13][14][15], as we also reported in our work. Therefore, detecting low-level RAS Y93H on the NS5A of Pt.2 at his baseline can be important to further stress the correlations, described by AADLS, between the presence of Y93H at the baseline in patients treated with sofosbuvir/velpatasvir and reduced SVR12 [4].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…outcomes [11][12][13][14][15], as we also reported in our work. Therefore, detecting low-level RAS Y93H on the NS5A of Pt.2 at his baseline can be important to further stress the correlations, described by AADLS, between the presence of Y93H at the baseline in patients treated with sofosbuvir/velpatasvir and reduced SVR12 [4].…”
Section: Discussionsupporting
confidence: 87%
“…Current clinical guidelines state that only RAS present at frequencies above 15% need to be considered when choosing antiviral treatments [4] since polymorphisms associated with drug resistance have been also demonstrated by Sanger for higher represented viral variants [9,10]. However, the detection threshold is still debated as studies showed different results when mutations at a frequency below 15% are investigated [4, [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For these drugs, not only is there different susceptibility among GTs, but also there is evidence of different resistance-associated-mutations (RAMs) development [ 7 , 9 ]. Importantly, NS5A RAMs have been described both before treatment (also called baseline) as well as after failure of NS5A inhibitors-containing therapies [ 10 , 11 , 12 , 13 , 14 , 15 ]. According to the current recommendations of the European Association for the Study of the Liver (EASL), resistance testing for NS5A inhibitors is subject to the availability of reliable tests, and the list of potential NS5A RAMs include several mutations in positions 28, 30, 31, 58, and 93 for GT-1a viruses and the mutation Y83H for the GT-3 viruses [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Q30R is known to confer resistance against multiple NS5A inhibitors for GT-1a viruses [ 16 , 17 , 23 , 24 , 25 ]. The substitution to a chemically similar lysine (K) has been observed to confer resistance both for GT-1a viruses [ 26 ] and for GT-3 viruses [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Viral RNA was extracted from serum samples using the automatic Easy Mag extractor (Biomerieux, Lyon, France). HCV NS5A domain I (aa 1-406), NS3-protease (aa 1-181), and NS5B (aa 1-591) genes were amplified using a nested RT-PCR [17,18]. The amplified NS5A region Viruses 2020, 12, 255 3 of 10 included PKR-bd (from aa 237 to 302) and ISDR (from aa 237 to 302).…”
Section: Hcv-rna Quantification and Sequencingmentioning
confidence: 99%